Evaluating Connectivity and Effectiveness of the Road Transportation Network in West Bangka Regency - Ilpandari Ilpandari; Singgih Hartanto; Junita Eka Susanti; Galih Rio Prayogi; Putri Ayu Dwiyana; Farah Mawaddah; Fas'ul Akbar (G-Tech: Jurnal Teknologi Terapan, 2026)
Transportation infrastructure is essential for regional integration and economic development in West Bangka Regency. However, corridor-oriented growth has led to uneven connectivity and a strong reliance on limited road corridors. This study evaluates the connectivity and effectiveness of the regional transportation network using spatial, topological, and operational indicators based on a graph representation comprising 12 links and 10 nodes that reflect the main inter-district road structure. The analysis integrates Alpha (α), Beta (β), and Gamma (γ) indices, road density, Accessibility Index (AI), Volume-to-Capacity (V/C) ratio, Level of Service (LOS), Travel Time Efficiency (TTE), and a composite Network Effectiveness Index (NEI). Results show low structural connectivity (Beta 0.20–0.33; Gamma 0.08–0.13; negative Alpha; density 0.039), indicating a tree-like configuration with minimal redundancy. Although operational performance remains stable (V/C 0.02–0.59; LOS A–C), accessibility is moderate to low (AI 0.189; travel time 90–111 minutes). The overall NEI indicates moderate effectiveness but limited network resilience. These findings highlight the need for policymakers to prioritize the development of alternative and transversal road links to reduce dependence on single corridors, improve accessibility, and strengthen long-term transportation resilience. The proposed approach provides a quantitative framework for infrastructure planning in corridor-dominated developing regions.